Concerto para fagote e orquestra de Danilo Guanais: uma abordagem técnico interpretativa - Santos, Alexandre dos (2018)
This study aims objective to investigate interpretative aspects of Danilo Guanais’s concert for bassoon and orchestra that are important for the performance of the work. Through the analysis of the composer’s techniques and procedures as well as the implicit information found in the musical text, we will seek to provide subsidies to support interpretative decisions that will be suggested for the bassoon parts. Danilo Guanais is currently one of the major composers from Rio Grande do Norte, with compositions such as "Missa" and "Paixão segundo Alcaçus" having reached prominence in the national and international music scene. His production includes works for guitar, orchestra, choir, theater and chamber music. In a good part of his compositions, the composer uses a methodology that combines modern compositional procedures with rhythmic, melodic and harmonic elements related to armorial music. Methodologically, this study is divided into two parts: the firs part includes an interview was made with the composer, a bibliographical survey and the selection and cataloging of the interpretative aspects to be studied. In the second part, an analysis of the work was carried out in order to elaborate interpretative suggestions for the bassoon parts. This investigation involves interpretative aspects to the bassoon so it can aid new interpretations in the construction of its performances of this work, as well as of other similar works.